Tolerância e eficiência de rizóbios nativos de área de mineração de manganês no desenvolvimento de leguminosas - Abreu, Marcos Giovane Pedroza de (2018)
Soil pollution by heavy metals occurs mainly due to poor management of wastes generated by mining during the exploitation and processing of metals, regarding to soil environment concern, this research aimed to: Evaluate the tolerance and the effectiveness of native rhizobium strains in soils of Mn mining areas in association with leguminous species grown under increasing concentrations of Mn. Initially, isolates of soil native rhizobia from the Mn mining area were obtained, with cowpea and sabiá as trap plants. Subsequently these isolates were authenticated and morphologically characterized. Two experiments were carried out using a natural soil to observe the effect of Mn on the leguminous species growth and nodulation, the evaluated variables were: number of nodules (NN); nodules dry mass (NDM); shoot dry matter mass (SDMM); shoot nitrogen content; manganese content in the aerial part of the plants and nitrogen accumulation in the aerial part (NAAP). Data were submitted to variance analysis. Qualitative variables were compared by the Scott-Knott test (p <0.05) and quantitative (doses) were submitted to regression analysis, using the statistical software Sisvar. 13 isolates were obtained for cowpea and 14 for the sabiá. Cowpea isolates presented variability in the morphological characteristics, medium pH, growth time, color and transparency of the colonies and elasticity, while sabiá isolates showed similarity to each other differing only in the form of the colonies. Mn did not affect the symbiotic process between rhizobia and cowpea, substrate soil native strains were equal to or greater than those isolated from Mn mining area, such as nodules dry matter, N content and accumulation. Mn significantly affected height, root dry matter and Mn content in the aerial part of the plants, increasing according to the levels of the metal in the soil. Regarding to sabiá, the Mn did not inhibit the symbiotic process with strains. The isolates from the mining area showed higher efficiency than the native strains in the production of SDMM, NN, NDM, N content and accumulation. Mn mining area isolates influenced the Mn content in the aerial part of the plants, decreasing its content according to Mn increments in soil. All rhizobial isolates from the degraded areas of manganese and substrate natives are tolerant to Mn and capable of inducing the formation of root nodules and fix nitrogen in cowpea (Vigna unguiculata L. Walp.) and sabiá (Mimosa caesalpiniaefolia Benth.). The native rhizobia of the substrate associated to the cowpea present intrinsic tolerance to Mn and are highly competitive. Isolates from the Mn mining degraded area, in symbiosis with sabiá, are able to increase this plants tolerance to soil Mn excess, through effective symbiosis and efficient N2 fixation, promoting plant growth.